2015
DOI: 10.1111/eci.12507
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in CYP‐mediated arachidonic acid routes affect the outcome of renal transplantation

Abstract: Taken together, these results indicate that variability in the CYP450 genes involved in the synthesis of eicosanoids from AA may have a significant impact on graft function and survival in renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Interestingly, in two other studies, the CYP2C8*3 variant in the Spanish recipients (not in donors) showed only a borderline association with DGF. These findings indicate that the relationship between this variant and the risk of DGF may be inconsistent in Spanish patients.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, in two other studies, the CYP2C8*3 variant in the Spanish recipients (not in donors) showed only a borderline association with DGF. These findings indicate that the relationship between this variant and the risk of DGF may be inconsistent in Spanish patients.…”
Section: Discussionmentioning
confidence: 82%
“…More recently, inactivating variants in CYP4F2 and CYP4A11 were associated with delayed graft function and post-transplant diabetes mellitus. 167,168 Similarly, variants in CYP2C8, CYP2J2, and sEH that reduce levels of EETs are associated with allograft dysfunction. [168][169][170] These results suggest that both 20-HETE and EETs may have a protective role in renal transplant.…”
Section: Transplantmentioning
confidence: 99%
“…Toll-like receptor 4 signaling has long been investigated as a mediator for renal fibrosis after transplantation and over the course of various nephropathies (36)(37)(38)(39)(40)(41). In contrast to that, derivatives of arachidonic acids and their mimics were shown to exhibit anti-fibrotic effects and polymorphisms in their CYP-dependent metabolism to influence susceptibility to renal injury (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%